(untitled) (Research, Society and Development, 2021)
Introduction: There is a high prevalence of the appearance of postoperative pain associated with endodontic and orthodontic treatment. Low-level laser therapy (LLLT) is a non-pharmacological method that has been suggested as an effective treatment to reduce this type of pain, with several advantages and the absence of side effects. Objective: To evaluate the efficacy of low-level laser therapy for the management of pain associated with endodontic and orthodontic treatment by reviewing relevant scientific articles. Methodology: An electronic search was carried out in the Pubmed database in the English language from 2011 to January 2021, of which 37 were fully analyzed for the present review. Conclusion: The use of LLLT for the control of postoperative pain associated with endodontic and orthodontic therapy would be effective and promising since, in addition to its analgesic effect, it offers other advantages in treatment, making it a valid option for routine clinical application.